PERBANDINGAN EFEKTIVITAS EKSTRAK BAWANG PUTIH (Allium sativum L.) DENGAN DAUN BAJAKAH (Uncaria acida Roxb.) SEBAGAI LARVASIDA VEKTOR DENGUE Aedes aegypti - Fitra Akbar Mulyono; Iqlila Romaidha; Nur Aini Hidayah Khasanah; Febri Nur Ngazizah (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2021)
Dengue fever is a disease caused by the dengue virus carried by the A. aegypti mosquito. Making natural larvicides from plants such as Alium sativum L. and Uncaria acida Roxb. are indispensable. This study aims to make natural larvicides from A. sativum and U. acida. This study is an experimental study using a Completely Randomized Design (CRD) to see the effectiveness of the extract A. sativum with U. acida as larvicide of the mosquito A. aegypti.This study used 20 mosquito larvae for each concentration and repeated 4 times. The results showed that the larvicide of A. sativum at the highest concentration reached 100% mortality, while the larvicide of U. acida at the highest concentration reaching 80% mosquito larvae death A. aegypti. Analysis of research data was processed using SPSS version 20. One Way Anova analysis of A. sativum extract was sig 0.049 and U. acida extract was sig 0.245. In the extract of A. sativum there was a significant difference in the mortality of mosquito larvae at each concentration, while in the extract of U. acida there was no significant difference in the mortality of mosquito larvae at each concentration. T-test analysis of the extracts of A. sativum and U. acida was sig 0.80, so there was no difference in effectiveness between the two larvicidal extracts. It can be concluded that the larvicidal research results of A. sativum extract and U. acida extract were equally effective on A. aegypti larvae.